2003
DOI: 10.1124/jpet.103.050625
|View full text |Cite
|
Sign up to set email alerts
|

Studies of μ-, κ-, and δ-Opioid Receptor Density and G Protein Activation in the Cortex and Thalamus of Monkeys

Abstract: The aim of this study was to investigate the relative density of -, -, and ␦-opioid receptors (MOR, KOR, and DOR) and guanosine 5Ј-O-(3-[

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 29 publications
4
22
0
Order By: Relevance
“…These results are similar to those reported in another study showing that naltrexone displayed 5-fold higher affinity than 6␤-naltrexol for sites labeled by [ 3 H]DAMGO in guinea pig brain homogenate (Nelson et al, 1994). To compare the in vitro antagonist potency of both compounds, [ 35 S]GTP␥S binding was used to provide a functional correlate of ligand-binding experiments (Traynor and Nahorski, 1995;Ko et al, 2003). DAMGO concentrationdependently increased the binding of [ 35 S]GTP␥S over basal by 52% in the monkey thalamus, consistent with previous findings that the MOR is abundant and the maximum of G protein activation by a MOR agonist can be observed in the primate thalamic region (Sim-Selley et al, 1999;Ko et al, 2003).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…These results are similar to those reported in another study showing that naltrexone displayed 5-fold higher affinity than 6␤-naltrexol for sites labeled by [ 3 H]DAMGO in guinea pig brain homogenate (Nelson et al, 1994). To compare the in vitro antagonist potency of both compounds, [ 35 S]GTP␥S binding was used to provide a functional correlate of ligand-binding experiments (Traynor and Nahorski, 1995;Ko et al, 2003). DAMGO concentrationdependently increased the binding of [ 35 S]GTP␥S over basal by 52% in the monkey thalamus, consistent with previous findings that the MOR is abundant and the maximum of G protein activation by a MOR agonist can be observed in the primate thalamic region (Sim-Selley et al, 1999;Ko et al, 2003).…”
Section: Discussionsupporting
confidence: 86%
“…Both cortical and thalamic membranes of monkeys were prepared according to the procedure described in a previous study (Ko et al, 2003). Cortical membranes (400 g of protein) of monkeys were incubated for 75 min at 25°C with 1 nM [ 3 H]DAMGO and varying concentrations of unlabeled 6␤-naltrexol or naltrexone (0.03-100 nM) in 50 mM Tris buffer, pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Behavioral and neurochemical studies have shown that SNC80 produces delta receptormediated effects in rhesus monkeys and has high intrinsic efficacy at delta receptors Brandt et al, 2001a;Ko et al, 2003). Previous research has demonstrated that delta opioid receptor agonists produce dose-dependent decreases in food-maintained behavior, and the potency to decrease food-maintained responding correlated with affinity at delta opioid receptors .…”
Section: Discussionmentioning
confidence: 99%